A 2, 7-dichlorofluorescein derivative to monitor microcalcifications. Issue 11 (19th October 2022) - Tholen, Patrik; Brown, Connor N.; Keil, Claudia; Bayir, Ali; Zeng, Hui-Hui; Haase, Hajo; Thompson, Richard B.; Lengyel, Imre; Yücesan, Gündoğ
Abstract : Herein, we report the crystal structure of 2, 7-dichlorofluorescein methyl ester (DCF-ME) and its fluorescence response to hydroxyapatite binding. Abstract : Herein, we report the crystal structure of 2, 7-dichlorofluorescein methyl ester (DCF-ME) and its fluorescence response to hydroxyapatite binding. The reported fluorophore is very selective for staining the bone matrix and provides turn-on fluorescence upon hydroxyapatite binding. The reported fluorophore can readily pass the cell membrane of the C2C12 cell line, and it is non-toxic for the cell line. The reported fluorophore DCF-ME may find applications in monitoring bone remodeling and microcalcification as an early diagnosis tool for breast cancer and age-related macular degeneration.